Off the grid - Box, C. J. (Box, C. J. Joe Pickett novel., 2016)
Joe Pickett's old friend Nate Romanowski is off the grid, recuperating from wounds and lying low while the FBI search for him. But they are not the only ones looking for him and Nate finds himself confronting an elite team of special forces soldiers. They're not there to take him in - they say - but to make a deal. They need his help destroying a domestic terror cell in Wyoming's Red Desert, and in return they'll make Nate's criminal record disappear. But Joe's not sure they can be trusted. And they can't. They have a very different plan in mind, and it just may be something that takes them all down--Nate and Joe included.